Manajemen Inovasi Pembelajaran Berbasis Media Interaktif Pada Satuan PAUD Se-Kota Serang - Siti Nur Amaliah; Rohayati; Eka Pidayasari; Hudaefah; Minhatul Ma’arif (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
The research employed a descriptive qualitative approach, supported by quantitative data in the form of percentage results obtained from field observations. Data were collected through direct observation of classroom learning processes, analysis of instructional planning documents, and the use of structured observation instruments. The findings indicate that the utilization of interactive media in early childhood learning falls within the moderate to good category, with the highest level of achievement observed in the application of media during core learning activities. However, the planning aspect of innovation and the availability of digital supporting facilities still require further improvement. Overall, the use of interactive media has a positive impact on children’s learning engagement, enthusiasm, and concentration. Nevertheless, its implementation has not yet reached an optimal level due to limitations in educators’ digital competencies and the absence of a strong and integrated innovation management system at the institutional level of early childhood education settings.